Ihtimām al-Islām wa ʼInāyatuh bi al-ʼIlm wa al-ʼUlamāʻ fī Ḍawʻ al-Qurʻān al-Karīm - Abd. Rahman Qishash (Al-Zahra : Journal for Islamic and Arabic Studies, 2003)
There is no denying that Islam since its inception has given a high place for science and the knowledgeable. The author in this paper proves the statement by giving the following explanation: the concept of science and wide-ranged, the position of science in Islam, the position of Theologian in Islam, scientific principles desired in Islam and some Islamic figures.